Mathematical Modelling Approach for Evaluation of Thermal Water Aquifers: A Case Study of Paipa Geothermal System - Chaparro, Iván; Sánchez, Yuly; Mehrvar, Mehrab; McCarthy, Lynda; Quiñones, Edgar; Robles, Emiro; Santos Granados, Germán Ricardo (Stanford School of Earth, Energy & Environmental Sciences, 2021)
The Paipa geothermal aquifer system, located in the axial zone of the eastern mountain range of Colombia, is the municipality's tourism industry base. Sedimentary rocks characterize the geology of the region, with some magmatic intrusions. This study presents a mathematical modelling approach of the system, considering information from secondary sources. The model shows that the information available is not sufficient to prepare a complete model. Data on the volumes exploited from the aquifer by the tourism industry is not sufficient. Furthermore, there is no information on pumping tests to establish the hydraulic conductivity of materials in the area. The results of the mathematical modelling approach show the relevance of alluvial deposits for the interaction between the geothermal system, the Chicamocha River, and Sochagota Lake. Also, it shows the relevance of the interaction between intrusions of magmatic origin and the groundwater flow within the aquifer, and the possibility of secondary permeability of this material. The simulation highlights the importance of the Tilatá formation, and the clay rocks of the Guaduas formation, in the behavior of the aquifer.
Digital
Keywords: Ingeniería geotérmica; Geothermal engineering; Hidrogeología; Hydrogeology; Aguas subterráneas; Groundwater; Geothermal; Groundwater; Modflow; MODELMUSE; Paipa; Sochagota